Leg stiffness and potential energy in the countermovement phase and the CMJ jump height - Struzik, A.; Zawadzki, J.; Rokita, A. (Biomedical Human Kinetics, 2016)
Study aim: The elastic potential energy accumulated in the musculotendinous units during the countermovement phase of a jump adds up to the energy supplied by the contracting muscles used in the take-off phase. Consequently, the total mechanical energy used during the jump may reach higher values. Stiffness represents a quantitative measure of a body`s elastic properties. Therefore, the aim of this study was to establish the relationship between leg stiffness and the countermovement jump height.